A Cross Correlation Between Karyotyping and Anthropometric Measurement of Down Syndrome at Malang, Indonesia - Antonius Christianto Christianto; Haryudi Aji Cahyono; Djoko Wahono Soemadtji; Fatchiyah Fatchiyah Fatchiyah (Biomedical Engineering, 2016)
Objective:   Herein, we reported a first study of Down syndrome chromosome analysis in Malang, Indonesia and correlation between phenotype, anthropometric measurement and karyotyping dataMaterial and methods: Karyotyping was conducted using peripheral blood culture.Result:   The karyotyping result showed that from nine patients with DS, we found two types of DS, trisomy 21 in seven patients and mosaicism in two patients. Interestingly, two patients with mosaicism have different percentages of cells with abnormal chromosomes (trisomy 21). In our cases, lower percentages of cells with abnormal chromosomes, the morphologies of patient were more likely normal control.Conclusion:    At least in, at least in part the ratio between lower and upper segment was proved to be different between normal and DS patients.